Interfacial Morphodynamics of Proliferating Microbial Communities - Alejandro Martínez-Calvo; Carolina Trenado-Yuste; Hyunseok Lee; Jeff Gore; Ned S. Wingreen; Sujit S. Datta (Physical Review X)
In microbial communities, various cell types often coexist by occupying distinct spatial domains. What determines the shape of the interface between such domains—which, in turn, influences the interactions between cells and overall community function? Here, we address this question by developing a continuum model of a 2D spatially structured microbial community with two distinct cell types. We find that, depending on the balance of the different cell proliferation rates and substrate friction coefficients, the interface between domains is either stable and smooth or unstable and develops fingerlike protrusions. We establish quantitative principles describing when these different interfacial behaviors arise and find good agreement with both the results of previous experimental reports as well as new experiments performed here. Our work, thus, helps to provide a biophysical basis for understanding the interfacial morphodynamics of proliferating microbial communities as well as a broader range of proliferating active systems.